EMOTIONAL INTELLIGENCE - Velasco Bernal, José Javier (2001)
The term emotional intelligence was first used in 1990 by Peter Salovey of Harvard and John Mayer of New Hampshire, as the ability to control and regulate the feelings of self and others and use them as a guide to thought and action . Emotional intelligence embodied in a wide range of skills and personality traits: empathy, understanding and expression of feelings, control our temper, independence, adaptability, empathy, ability to solve problems in an interpersonal, social skills, persistence, warmth, kindness and respect.